2011
DOI: 10.1071/sr10023
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of soil water storage evaluated for a coffee field

Abstract: Abstract. Sampling field soils to estimate soil water content and soil water storage (S) is difficult due to the spatial variability of these variables, which demands a large number of sampling points. Also, the methodology employed in most cases is invasive and destructive, so that sampling in the same positions at different times is impossible. However, neutron moderation, time domain reflectrometry, and, more recently, frequency domain reflectrometry methodologies allow measurements at the same points over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
7
12
0
Order By: Relevance
“…8(b and c) and 9(b and c)). Timm et al (2011) also reported similar findings when 50% and 75% of data were omitted during state-time analysis of soil water storage, evapotranspiration and precipitation in a coffee field in Brazil. Fig.…”
Section: Temporal Processes Of Soil Temperaturesupporting
confidence: 75%
See 1 more Smart Citation
“…8(b and c) and 9(b and c)). Timm et al (2011) also reported similar findings when 50% and 75% of data were omitted during state-time analysis of soil water storage, evapotranspiration and precipitation in a coffee field in Brazil. Fig.…”
Section: Temporal Processes Of Soil Temperaturesupporting
confidence: 75%
“…These results of this study agreed with findings of a similar study by Dourado-Neto et al (1999) on state-space analysis of soil water content and temperature in a sugarcane field. Likewise, Timm et al (2011) working on temporal variability of soil water storage of an irrigated-coffee field found higher coefficients of determination in estimating soil water storage by state-time analysis in comparison to classical multiple regression. The state-time analysis also revealed that, since the observation of a variable is an estimate of its true value, the analysis automatically considers that each measurement possesses an explicit observation as well as model error (denoted as v t ) (Nielsen and Wendroth, 2003).…”
Section: Temporal Processes Of Soil Temperaturementioning
confidence: 95%
“…Spearman rank correlation coefficients of soil moisture between different dates were in general significant at P b 0.05 except for a few cases (data not shown), implying that θ tended to be temporally stable to some extent at different times as also observed for 0-1.0 m soil water storage in a coffee field (Timm et al, 2011). The relatively lower Spearman rank correlation coefficients usually corresponded to the greater values of RE%, and vice versa (Fig.…”
Section: Temporal Change Of Soil Moisturesupporting
confidence: 49%
“…Its distribution is the main object of study in investigations into the water balance of the different layers present in a soil profile (CRUZ et al, 2005;PARAJKA et al, 2006;PENNA et al, 2009). However, one of the biggest challenges facing these investigations relates to estimating the soil water content, since in the field there is significant variability of both space and time (GAO et al, 2011;TIMM et al, 2011), mainly arising from the variability of both the physical and water characteristics of the soil (CAJAZEIRA; ASSIS JUNIOR, 2011). To this end, the spatial variability of these properties must be well known in order to minimize errors when taking samples and in soil management (GREGO;VIEIRA, 2005;SOUZA et al, 2004).…”
Section: Introductionmentioning
confidence: 99%